2020
DOI: 10.1111/cdev.13365
|View full text |Cite
|
Sign up to set email alerts
|

How Heritable are Parental Sensitivity and Limit‐Setting? A Longitudinal Child‐Based Twin Study on Observed Parenting

Abstract: We examined the relative contribution of genetic, shared environmental and non-shared environmental factors to the covariance between parental sensitivity and limit-setting observed twice in a longitudinal study using a child-based twin design. Parental sensitivity and parental limit-setting were observed in 236 parents with each of their same-sex toddler twin children (M age = 3.8 years; 58% monozygotic). Bivariate behavioral genetic models indicated substantial effects of similar shared environmental factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 64 publications
2
20
0
Order By: Relevance
“…Our findings converge with several previous non-intervention studies indicating that the majority of the variance in observed parenting behaviors can be explained by shared environmental factors, with only small or non-significant child genetic effects [ 4 8 ]. For example, Euser et al [ 5 ] reported a behavioral genetics analysis of parental sensitivity and limit-setting on the pretest data of the current study (Wave 1 and Wave 2), showing little child-based genetic influences on parenting. The VIPP-SD intervention impacted parental sensitive limit setting of both children in the family in a similar way.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Our findings converge with several previous non-intervention studies indicating that the majority of the variance in observed parenting behaviors can be explained by shared environmental factors, with only small or non-significant child genetic effects [ 4 8 ]. For example, Euser et al [ 5 ] reported a behavioral genetics analysis of parental sensitivity and limit-setting on the pretest data of the current study (Wave 1 and Wave 2), showing little child-based genetic influences on parenting. The VIPP-SD intervention impacted parental sensitive limit setting of both children in the family in a similar way.…”
Section: Discussionmentioning
confidence: 66%
“…For parental sensitivity, within-twin correlations ranged between r = .59 and r = .62 for the different waves and correlations across time ranged between r = .40 and r = .60 for the two children and different waves. Within-twin correlations were comparable for parental sensitive limit-setting, ranging between r = .56 and r = .60 for the different waves, but across-time correlations were somewhat lower, ranging between r = .19 and r = .47 for the two children and different waves (see Euser et al [ 5 ] for a behavioral genetics analysis).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Parents who have healthy communication with their children can be considered empathetic [ 31 ], and healthy communication plays a protective role in children’s engagement in risky behaviors [ 32 ]. Limit setting is considered a parenting discipline technique for establishing appropriate behaviors in children [ 33 ]. Children with parents who do not establish limits for them may feel insecure and are more likely to exhibit problematic behaviors [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it seems a plausible but potentially disturbing hypothesis that heritability might play a role in parenting (Euser et al, in press) and more specifically in intergenerational transmission of child maltreatment (Pittner et al, ). Heritability can be misunderstood to imply that children are to blame for their own maltreatment.…”
Section: Discussionmentioning
confidence: 99%